Media Penunjang Pembelajaran Organ Paru-Paru Manusia Berbasis Mobile Menggunakan Augmented Reality (Studi Kasus SDN 2 Ardimulyo) - Danni Nur Cahyani; Chaulina Alfianti Oktavia (J-INTECH ( Journal of Information and Technology), 2019)
Interest in reading Indonesian people, especially children is still very minimal. So that makes the development of students' interest in reading ability is very alarming. This is because the method given to students is not optimal. The low interest in reading for students becomes a habit, thus affecting students' reading ability. Efforts to encourage interest in reading begin with simple things like changing the learning patterns that initially used the media of books to be more interesting by using Augmented Reality technology. With this technology, it is hoped that students can be active in following the learning process and students will be more interested in deepening science lessons, especially the lungs. In this learning media, there are 4 main features namely lung anatomy, lung function, pulmonary disease and, help menu. In utilizing this technology, it has been proven that this learning support media uses language that is easily understood by students so that students' enthusiasm for learning can increase.